ESTUDO QUÍMICO E ATIVIDADE ANTIFÚNGICA DO ÓLEO ESSENCIAL DOS FRUTOS DA Pimenta dioica Lindl. - B. Júnior, Francisco Reivilandio da S. (2011)
Jamaican pepper, Pimenta dioica Lindl, is a species belonging to the family of Myrtacea, measuring 6m to 15m high, very aromatic in all its parts. It is originally from Central America and West India and with great economic importance in the market of essential oils. The extraction of the essential oil of Pimenta dioica L seeds was carried out by using the method of hydrodistillation known as Cleverger system. It was extracted from a maximum volume of oil in the period of four hours with a yield of 2.8% m/m. The UV spectrophotometric techniques, mass spectrometry and gas chromatography, as well as the physical constants, density, color and appearance were used to identify the compound eugenol and other constituents of the essential oil of P. dioica L. Through the technique of external standard and standard addition it was quantified with a eugenol percentage of 76.98%, forming the major component. The essential oil of Pimenta dioica L was applied to the phyto pathogenic fungi species Fusarium oxysporum f. sp. lycopersici, Fusarium oxysporum f. sp. passiflorae, Fusarium subglutinans f. sp ananas., Fusarium oxysporum f. sp. vasinfectum and Fusarium oxysporum f. sp. cubense resulting in a total inhibition of mycelial growth of all species tested for a period of ten days of evaluation.